APOL1 risk variants and kidney disease: what we know so far - Tobias August Siemens; Miguel Carlos Riella; Thyago Proença de Moraes; Cristian Vidal Riella (Brazilian Journal of Nephrology, 2018)
ABSTRACT There are striking differences in chronic kidney disease between Caucasians and African descendants. It was widely accepted that this occurred due to socioeconomic factors, but recent studies show that apolipoprotein L-1 (APOL1) gene variants are strongly associated with focal segmental glomerulosclerosis, HIV-associated nephropathy, hypertensive nephrosclerosis, and lupus nephritis in the African American population. These variants made their way to South America trough intercontinental slave traffic and conferred an evolutionary advantage to the carries by protecting against forms of trypanosomiasis, but at the expense of an increased risk of kidney disease. The effect of the variants does not seem to be related to their serum concentration, but rather to local action on the podocytes. Risk variants are also important in renal transplantation, since grafts from donors with risk variants present worse survival.